Propuesta para el diseño de un plan de marketing digital para la empresa “coser y tejer de la costa” en la ciudad de fundación magdalena (2024)
This thesis presents a detailed analysis and proposal of a Strategic Digital Marketing Plan designed specifically for the company "Coser y Tejer de la Costa", based in the city of Fundación Magdalena. The main objective is to improve the company's online presence and enhance its positioning in the market, taking advantage of the opportunities offered by the digital environment. The study begins with an exhaustive review of the business context, identifying the characteristics of the textile sector in the region and evaluating the company's current presence on digital platforms. Through market analysis tools, consumer trends and preferences in the digital sphere are identified. Subsequently, a comprehensive digital marketing strategy is developed that covers aspects such as website optimization, the effective use of social networks, the implementation of online advertising campaigns and content management. Specific tactics are also proposed to improve customer interaction, foster loyalty and increase brand visibility. In summary, this thesis provides a practical and detailed approach to implementing a Strategic Digital Marketing Plan adapted to the specific needs and characteristics of "Coser y Tejer de la Costa". The application of these strategies not only seeks to strengthen the company's online presence, but also improve its competitiveness and contribute to sustainable growth in the local and digital market